👤

Calculer en détaillant les étapes :

B = 6 x [13 (5-2)]

C= [(8-2) x 8] ÷ 4+8

D= [(31 - 5) - 2 x 7)] ÷ 6 ÷ 2







Répondre :

Bonjour,

N'oublies pas la formule de politesse la prochaine fois ;)

Rappel :

+ et + = +

+ et - = -

- et - = +

Priorités : parenthèses // x et : // + et -

Donc :

B = 6 x [13 (5-2)]

B = 6 x ( 13 x 3)

B = 6 x 39

B = 234

C= [(8-2) x 8] ÷ 4+8

C = ( 6 x 8 ) ÷ 4+8

C = 48 ÷ 4+8

C = 12 + 8

C = 20

D= [(31 - 5) - 2 x 7)] ÷ 6 ÷ 2

D = [26 - 14] ÷ 6 ÷ 2

D = 12 : 6 : 2

D = 2 : 2

D = 1

Bonne journée.